AB mix, Kalium, Selada PERTUMBUHAN DAN HASIL SELADA (Lactuca sativa L.) DALAM KULTUR HARA PADA BERBAGAI KONSENTRASI LARUTAN AB MIX DAN KALIUM - Fifi Mutia; Ruli Joko Purwanto; Karlin Agustina (Universitas Muhammadiyah Bengkulu, 2026)
The performance of hydroponic lettuce cultivation significantly depends on the precision of nutrient solution formulation, thus requiring the availability of nutrient elements in an optimal composition with high bioavailability. In hydroponic systems, AB Mix nutrients, which consist of two solution components (A and B), have become the standard application. Potassium, as an essential macronutrient, plays a crucial role in plant growth, particularly through enzymatic activation mechanisms that support metabolic processes and cellular biosynthesis. One of the challenges in hydroponic lettuce cultivation is the unknown optimal nutrient dosage and relatively high nutrient prices. The impact of K fertilizer application on the development and yield of lettuce plants is influenced by the amount of nutrient elements supplied through AB mix fertilizer, as well as the concentration levels used. This study aims to determine the concentration of AB mix nutrients and the addition of K fertilizer on the growth and yield of lettuce (Lactuca sativa L.) in a hydroponic setting. This research was conducted at The Zafarm. The method used in this study is a Randomized Block Design (RBD) with one factor divided into 9 treatment levels. Each treatment was conducted with three repetitions, resulting in a total of 27 experimental units. Since each unit consists of 4 individual plants, the total number of plants used is 108. The results of this study concluded that the application of AB mix general vegetable fertilizer at 1200 ppm + Potassium 250 ppm provides the best lettuce plant results, which can be measured by the increase in plant height, leaf area development, fresh weight, dry weight, as well as root length and volume, and dark green color, sweet taste, and crispy texture. The application of artificial formulation AB mix fertilizer has not been able to match the growth of plants using AB mix general vegetable fertilizer across all variables.